?? Statistical convergence of order ? on time scales - Er, Busra Nur; Altin, Yavuz (Universitatea din Craiova, 2022)
In this study, we introduce the notions ?? -statistical convergence of order ? (for ? ? (0, 1]) and an summability of order ? (for ? ? (0, 1]) on an arbitrary time scale. Moreover, some relations about these notions are obtained. We define ?? -statistical boundedness of order ? (for ? ? (0, 1]) on a time scale. Furthermore, we give connections between (Formula Presented) for various sequences (Formula Presented)and (Formula Presented) which are determined in class ? © 2022,Annals of the University of Craiova, Mathematics and Computer Science Series. All Rights Reserved.
Keywords: sequence spaces; statistical boundedness; Statistical convergence; time scales